Polar Eskimo Genealogy. - Gilberg, Aage; Gilberg, Lisbet; Gilberg, Rolf; Holm, Mogens (Meddelelser om Grønland, 1978)
For half a century information on the genealogy of the Polar Eskimos has been collected from all possible sources by the authors. In this way the Polar Eskimo Genealogy, presented here, goes back 6-7 generations in several cases from December 31, 1973 to the middle of the nineteenth century. In order to store this huge amount of genealogical information and to be able to follow the kinship relations a special family diagram combined with a code system has been developed. The main part of this article is made up of 630 family diagrams containing the genealogical data for each Polar Eskimo nuclear family separately, in such a way that family relationships can easily be followed in all directions. An explanation to the code system is found in front of the family diagrams. Polar Eskimo genetical and anthropological data (collected in 1963) are given in tables in four appendices: (A) Polar Eskimo Blood Groups. (B) Polar Eskimo Finger- and Palmprints. (C) Polar Eskimo Eye and Earlobe data. (D) Polar Eskimo anthropometrical data. The code system makes it possible to use the genealogy and the genetical markers together.